Vulnerability of Street Trees in Upper Midwest Cities to Climate Change - Brandt, Leslie A.; Johnson, Gary R.; North, Eric A.; Faje, Jack; Rutledge, Annamarie (Frontiers in Ecology and Evolution, 2021)
Urban trees play an important role in helping cities adapt to climate change, but also are vulnerable to changes in climate themselves. We developed an approach for assessing vulnerability of urban tree species and cultivars commonly planted in cities in the US Upper Midwest to current and projected climate change through the end of the 21st century. One hundred seventy-eight tree species were evaluated for their adaptive capacity to a suite of current and future-projected climate and urban stressors using a weighted scoring system based on an extensive literature review. These scores were then evaluated and adjusted by leading experts in arboriculture in the region. Each species or cultivar’s USDA hardiness zone and American Horticultural Society heat zone tolerance was compared to current and future heat and hardiness zones for 14 municipalities across Michigan, Wisconsin, and Minnesota using statistically downscaled climate data. Species adaptive capacity and zone tolerance was combined to assign each species one of five vulnerability categories for each location. We determined the number of species and trees in each category based on the most recent municipal street tree data for each location. Under a scenario of less climate change (RCP 4.5), fewer than 2% of trees in each municipality were considered highly vulnerable across all 14 municipalities. Under a scenario of greater change (RCP 8.5), upwards of 25% of trees were considered highly vulnerable in some locations. However, the number of vulnerable trees varied greatly by location, primarily because of differences in projected summer high temperatures rather than differences in species composition. Urban foresters can use this information as a complement to other more traditional considerations used when selecting trees for planting.